Board heterogeneity and corporate performance: An insight beyond agency issues - Farheen Akram; Muhammad Abrar Ul Haq; Vinodh K Natarajan; R. Stephen Chellakan (Cogent Business & Management, 2020)
In current volatile business environment, the owners of the corporations are worried about how diverse board composition influences the strategic performance of the corporations. Therefore, this study considered the agency theory, upper echelon and resource-based view of board heterogeneity as limited literature account for such integrated phenomenon of theories. Accordingly, the key aim of the study is to scrutinize the impacts of occupational heterogeneity (educational) and social heterogeneity (gender and national) on firm performance. At first, Blau's heterogeneity index was applied to measure the occupational heterogeneity and social heterogeneity, then ordinary least square method was applied for analysis. The data set was obtained from the non-financial sector of Pakistan Stock Exchange for the years 2010-2016 with final sample of 375 firms. The findings of current research concluded that all measures of occupational heterogeneity significantly and positively contribute to firm value expect finance education and other education (defense, arts, political science etc.). However, in social heterogeneity, gender diversity has a negative effect on firm performance while nationally heterogeneous board demonstrate a positive effect on firm performance. Moreover, this study has beneficial implications for the corporate sector as firms can boost their profitability by extracting benefits from their diverse workforce.
Keywords: 650; Educational heterogeneity of board; national heterogeneity; gender heterogeneity; firm performance